GOTHIC FIELDING? PHILIP JAMES DE LOUTHERBOURG’S TOM JONES - Lipski, Jakub (Porównania, 2018)
This article confronts P.J. de Loutherbourg’s drawings of the selected scenes from Tom Jones with the possible “Gothic” content in Henry Fielding’s novel. Commenting on Fielding’s pictorialism, I argue that the most suitable scene from Tom Jones would have been the actual Gothic mansion of Mr. Allworthy, but the scene does not attract the illustrator’s attention. Then, I discuss de Loutherbourg’s patterns of Gothicizing the selected scenes in the manner of Salvator Rosa, which in the original depend on the mock-heroic or the grotesque. The article concludes with raising more general questions about the paradigms of de-contextualization and re-contextualization in late 18th century print market and book illustration.